2004
DOI: 10.1007/s10563-004-9118-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective skeletal isomerization of alkanes over partially reduced MoO3

Abstract: The surface area and the pentane isomerization activity of Pt/MoO 3 were enlarged by H 2 reduction. The enlargements was observed only when the reduction proceeded through the formation of hydrogen molybdenum bronze, H x MoO 3 . The catalytic activities of H 2 -reduced MoO 3 with different noble metals for pentane isomerization and 2-propanol dehydration depended on the ability of noble metal to produce the H x MoO 3 phases. H 2 -reduced Pt/MoO 3 was more active for pentane isomerization than Pt/ Hb, and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Katrib et al , have also suggested that isomerization on oxycarbides proceeds by a bifunctional mechanism in which the active phase is a bifunctional MoO 2 (H x ) phase having Brønsted acid sites (Mo–OHx groups) on the surface and metallic sites (delocalized π electrons along the c axis of the Mo atoms in a MoO 2 distorted rutile phase). Matsuda et al , in their studies of the isomerization of n -heptane with partially reduced MoO 3 and considering the similarity between the kinetic parameters on MoO 1.54 with those of Pt/zeolite catalysts proposed that isomerization is carried out via a bifunctional mechanism by a H x MoO 3 phase, concluding that Mo metal was responsible for the dehydrogenation step and that MoO x H y was responsible for the isomerization step. Lamic et al in their studies with Mo and W carbides observed a product distribution in agreement with a bifunctional isomerization and concluded that MoC and WC act as the dehydrogenating function and W–OH acts as the acid function.…”
Section: Introductionmentioning
confidence: 99%
“…Katrib et al , have also suggested that isomerization on oxycarbides proceeds by a bifunctional mechanism in which the active phase is a bifunctional MoO 2 (H x ) phase having Brønsted acid sites (Mo–OHx groups) on the surface and metallic sites (delocalized π electrons along the c axis of the Mo atoms in a MoO 2 distorted rutile phase). Matsuda et al , in their studies of the isomerization of n -heptane with partially reduced MoO 3 and considering the similarity between the kinetic parameters on MoO 1.54 with those of Pt/zeolite catalysts proposed that isomerization is carried out via a bifunctional mechanism by a H x MoO 3 phase, concluding that Mo metal was responsible for the dehydrogenation step and that MoO x H y was responsible for the isomerization step. Lamic et al in their studies with Mo and W carbides observed a product distribution in agreement with a bifunctional isomerization and concluded that MoC and WC act as the dehydrogenating function and W–OH acts as the acid function.…”
Section: Introductionmentioning
confidence: 99%